1993
DOI: 10.1111/j.1574-6968.1993.tb06566.x
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive involvement of methyl ricinoleate β-oxidation in the production of γ-decalactone by the yeastPichia guilliermondii

Abstract: Production of γ‐decalactone by yeasts from fatty acids has been reported but little is known about the mechanisms involved in this process. This paper provides information about the mechanisms involved in the production of γ‐decalactone by Pichia guilliermondii in the presence of a fatty acid methyl ester. Culturing of P. guilliermondii in media containing methyl ricinoleate (12(R)‐hydroxy‐9(Z)‐octadecenoic acid) revealed a coordinated induction of β‐oxidation activities and γ‐decalactone production. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The production was reduced for higher castor oil contents (30, 40, 50, and 60 g/l). Similar results have been reported by Endrizzi et al [21], who observed that a high concentration of ricinoleic acid methyl ester lowers the yield of γ-decalactone produced by Pichia guilliermondii. However, our results contrasted with those reported by Dufossé et al [15], who showed that γ-decalactone concentration obtained in the culture broth of Sporidiobolus ruinenii increased almost proportionally with a ricinoleic acid methyl ester concentration between 0 and 160 g/l.…”
Section: Influence Of Initial Phsupporting
confidence: 87%
See 1 more Smart Citation
“…The production was reduced for higher castor oil contents (30, 40, 50, and 60 g/l). Similar results have been reported by Endrizzi et al [21], who observed that a high concentration of ricinoleic acid methyl ester lowers the yield of γ-decalactone produced by Pichia guilliermondii. However, our results contrasted with those reported by Dufossé et al [15], who showed that γ-decalactone concentration obtained in the culture broth of Sporidiobolus ruinenii increased almost proportionally with a ricinoleic acid methyl ester concentration between 0 and 160 g/l.…”
Section: Influence Of Initial Phsupporting
confidence: 87%
“…Indeed, peroxysomal β-oxidation enzymes were shown to be responsible for γ-decalactone production in other yeast strains [7,21,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, GDL reconsumption was observed due to Aox3 activity, which led to an increased 3-OH-GDL production. GDL reconsumption has been reported as an issue in older studies (Aguedo et al 2005;Endrizzi et al 1993;Waché et al 2001). Braga et al (2015a) compared lactone production profiles by Y. lipolytica W29 and two W29 mutants, MTLY40-2P (POX3-5 disrupted and POX2 overexpressed) and JMY3010.…”
Section: Lactonesmentioning
confidence: 99%